Outcome of Palliative Surgery in Advanced Pancreatic Cancer in Sudanese Patients in Ibn Sina Specialized Hospital - Alamin, Dalias M; Arabi, Nassir Alhaboob; Magid M, Abdul Musaad; A, Elsaggad Altayeb (Gezira Journal of Health Sciences, 2019)
Introduction: Pancreatic cancer is the 4 th leading cause of death and due to late presentation, the curative procedures are more challenging and difficult. Pancreatic cancer is not uncommon in Sudanese patients and usually presents late. The aim of this study was to assess the outcome of palliative surgery in advanced pancreatic cancer and to reflect our local experience. Methodology: It was a prospective cross-sectional hospital-based study.  It included 92 patients with advanced pancreatic cancer in Ibn Sina Specialized Hospital. Data were collected and variables; age, gender, origin and clinical features were measured. Patients were classified based on type of surgery (single, double or triplebypass). Data collected and analyzed by using statistical package for social sciences (SPSS) computer program version 20.Qualitative data were analyzed by using descriptive statistic t test and pearson chi_square. The P value was considered significant if <0.05. Results: The mean age of the study was 65.4, (+/_13SD)male to female ratio was 1.8:1. The majority of the patients (36%) were from northern state; namely Shwaiga, Mahas, Bederia and Gaalian and 22% from Western state namely Baggara, Jamoaia and Foor. Nearly two-third of the patients had double bypass, and the remaining were equally single and triple bypass. The main presenting symptoms were jaundice, dyspepsia and vomiting and it is significantly common among alcohol consumers. Dyspepsia was statistically early symptoms and serum aspartate transaminase (AST) and alkaline phosphatase (ALP) were statistically high. There was less than 30 % of those who survived more than one year. There was no statistically significant difference between type of bypass and the outcome. Conclusion: The outcome of those patients was not affected by modality of bypass. Dyspepsia was the earliest complain and high serum aspartate transaminase (AST) and alkaline phosphatase (ALP) could be important prognostic factors. pancreatic cancer is common in certain populations.